Can Piaget, Freud or Erikson explain my self-development? Pre-service teachers' personal evaluation - Zeren, S. Gonca (ELSEVIER SCIENCE BV, 2012)
The purpose of this study is to understand how pre-service teachers evaluate their personal development on the basis of their experiences. Participants' written texts within the context of the Developmental Psychology course formed the data in this study. Pre-service teachers have interpreted their own experiences within the framework of theories of classical theorists in developmental psychology such as Piaget, Freud and Erikson. Pre-service teachers stated that this personal evaluation process allowed them to increase their self-awareness and to be more understanding towards children and youngsters. It is suggested that using such kind of stories in teacher education will contribute positively to professional development of pre-service teachers. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Personal evaluation; pre-service teachers; developmental psychology; self-awareness; identity; story; Education & Educational Research